Current approaches to the treatment of viral infections in gynecology - L V Posiseeva (IP Berlin A.V., 2015)
The deterioration of women's reproductive health in recent years all over the world is due to the steady growth of the virus of genital infections and above all - herpes and human papillomavirus, leading to severe genital lesions, complications of pregnancy and perinatal pathology. The treatment of viral infection is a challenge, due to the damage to the immune system in patients. Review of the literature demonstrates the feasibility of using antiviral drugs, interferons and immune modulators to reduce or prevent the likelihood of emergence of resistant mutants of herpes viruses and human papillomavirus and increase the effectiveness of therapy.